Reduction of PAPR in OFDM Signals by using Electromagnetism Optimization Algorithm - Padma, R.; Kishore, K.Krishna (International Journal of Scientific Research and Management (IJSRM), 2015)
Orthogonal Frequency Division Multiplexing grown to be a trendy modulation process inside impressive tempo wirelesscommunications. It is more advantageous over remaining technologies, even though it has some problems also. The high PAPR (Peak toAverage Power Ratio) is the main difficulty which causes non linearity at the receiving end. To reduce the PAPR so many techniques areproposed in previous such as clipping and filtering, SLM, CE, SA, PTS and so on. PTS (Partial Transmit Sequence) is highly successive thananother. In this paper PTS technique is used to reduce the PAPR but there is one problem with PTS technique, it introduces a high amount of complexity. So that to reduce such complexity and get better PAPR we planned to implement a novel based stochastic optimization algorithm which is EM (Electromagnetism-like) algorithm. By using EM get the better PAPR than PTS